2003
DOI: 10.1149/1.1598964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Field on Electrode Reactions and Properties of Electrodeposited NiFe Films

Abstract: Enhancement of current for solutions, containing Ni+2, Fe+2, and H+ ions, has been observed by linear sweep voltammetry and chronoamperometry when a magnetic field of 0.1 T was applied parallel to the cathode. The current enhancement in a magnetic field was attributed to the convection near the electrode surface induced by the Lorentz force. There is a decrease of the Fe content in NiFe films by approximately 4% obtained with applied magnetic field. It was also demonstrated that the applied magnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…2 The application of a magnetic field during deposition of these ferromagnetic metals or alloys may introduce crystallographic or atomic-scale texture, which can influence the anisotropy and magnetic reversal in the electrodeposited material. [3][4][5] More recently, there have been reports of structuring of electrodeposits from paramagnetic solutions such as Cu 2þ using nonuniform magnetic fields produced by permanent magnets, 6,7 or soft iron, which is magnetized in an external field. 8,9 These studies establish that it is the magnetic susceptibility of the electroactive species, not the susceptibility of the electrolyte itself, which determines the pattern.…”
Section: Magnetic Structuring Of Linear Copper Electrodepositsmentioning
confidence: 99%
“…2 The application of a magnetic field during deposition of these ferromagnetic metals or alloys may introduce crystallographic or atomic-scale texture, which can influence the anisotropy and magnetic reversal in the electrodeposited material. [3][4][5] More recently, there have been reports of structuring of electrodeposits from paramagnetic solutions such as Cu 2þ using nonuniform magnetic fields produced by permanent magnets, 6,7 or soft iron, which is magnetized in an external field. 8,9 These studies establish that it is the magnetic susceptibility of the electroactive species, not the susceptibility of the electrolyte itself, which determines the pattern.…”
Section: Magnetic Structuring Of Linear Copper Electrodepositsmentioning
confidence: 99%
“…A number of research groups have reported some unique phenomena during electrodeposition in a magnetic field. [5][6][7][8][9][10][11][12][13][14][15] When an electrodeposition is conducted in a magnetic field, the magnetohydrodynamic (MHD) convection is induced by Lorenz force. Devos et al 16) reported that the surface morphology of electrodeposited Ni film was smoothed and the preferred orientation was drastically changed from (200) in 0 T to (220) in 5 T. These phenomena were explained by MHD convection that enhanced the mass transfer of organic additives near the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…The small grains belong to the sample deposited with light under magnetic field. Decreasing grain size with applying magnetic field was observed during the electrodeposition assisted by applied magnetic fields [19,20].…”
Section: X-ray Diffractionmentioning
confidence: 95%